2001
DOI: 10.1016/s0014-5793(00)02434-0
|View full text |Cite
|
Sign up to set email alerts
|

Human casein kinase Iδ phosphorylation of human circadian clock proteins period 1 and 2

Abstract: Casein kinase IO O (CKIO O), a central component of the circadian clock, interacts with and phosphorylates human period protein 1 (hPER1) NeuroReport 5, 951^955]. A mutation in CKIO O causes a shortened circadian period in Syrian Golden hamster. We have now extended our previous studies to show that human casein kinase IN N (hCKIN N), the closest homologue to hCKIO O, associates with and phosphorylates hPER1 and causes protein instability. Furthermore, we observed that both hCKIN N and hCKIO O phosphorylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 26 publications
7
92
1
1
Order By: Relevance
“…This enhanced nuclear localization may be due to a net increase in overall cellular PER concentrations, as a consequence of the reduced degradation of the PER target by CK1 inhibition (20). CK1-mediated phosphorylation of PER is known to affect nuclear translocation of the protein (9)(10)(11) and therefore may also contribute to the nuclear retention we observed.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This enhanced nuclear localization may be due to a net increase in overall cellular PER concentrations, as a consequence of the reduced degradation of the PER target by CK1 inhibition (20). CK1-mediated phosphorylation of PER is known to affect nuclear translocation of the protein (9)(10)(11) and therefore may also contribute to the nuclear retention we observed.…”
Section: Discussionmentioning
confidence: 71%
“…In Drosophila, mutations of doubletime (dbt, an ortholog of mammalian CK1) result in either short (dbt s ) or long (dbt l ) circadian rhythms (6,7). In mammals, both CK1ε and CK1δ can complex with PER and CRY (8) and phosphorylate PER proteins, leading to proteasome-mediated degradation and nuclear translocation (9)(10)(11). In humans, familial advanced sleep phase syndrome (FASPS) is associated with a T44A missense mutation in CK1δ, leading to hypophosphorylation of PER2 in vitro (12), although in Syrian hamsters and mice, the CK1ε tau mutation results in hyperphosphorylation and subsequent destabilization of its PER targets with significant shortening of behavioral activity cycles to 20 h (13-16).…”
mentioning
confidence: 99%
“…Indeed, it has been demonstrated that CKIε and CKIδ are involved in the phosphorylation of the mammalian PER proteins (Keesler et al 2000;Camacho et al 2001;Akashi et al 2002;Schlosser et al 2005). Moreover, CKIε is able to phosphorylate BMAL1 and CRY proteins in vitro (Eide et al 2002).…”
Section: Kinases and Phosphatasesmentioning
confidence: 99%
“…In a very similar manner, mammalian PER proteins are extensively phosphorylated by CKIε and CKIδ, thereby reducing the stability of the proteins by targeting them for proteasomal degradation (Keesler et al 2000;Camacho et al 2001;Akashi et al 2002). PER proteins are recognized by the Slimb homologs β-TrCP1/2 as parts of the SCF ubiquitin ligase complex.…”
Section: Phosphorylation Regulates Subcellular Localizationmentioning
confidence: 99%
“…52 In addition, the PAR-leucine zipper transcription factor albumin D element-binding protein (DBP) is a first-order clock-controlled gene directly regulated by BMAL1/ CLOCK; 53 it also plays a role in the core clock by activating Per1 transcription. 54 Kinases such as CKId, 55,56 CKIe 57,58 and GSK3b 25,59 play an important role in phosphorylation of clock proteins, thus regulating the activity, nuclear entry and degradation of various core clock components. Among these kinases, GSK3b is of particular interest here because it was reported to be one of the direct targets of lithium, 60 which is an effective therapy for bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%